Clinical features and recurrent attack in gout patients according to serum urate levels during an acute attack - Lee, Jung Sun (Korean J Intern Med, 2020)
BACKGROUND/AIMS: A substantial portion of gout patients have normal serum urate levels during an acute attack but data on the clinical characteristics and risk of recurrence compared with hyperuricemic patients are limited. METHODS: In this retrospective cohort study, clinical features of normouricemic and hyperuricemic patients were compared. Multivariate analysis was performed to determine whether normouricemic patients were less likely to have a recurrent attack. RESULTS: Among a total of 221 gout patients, 88 (39.8%) had normouricemia during an acute attack. Postsurgical gout (22.7% vs. 6.0%, p < 0.001), hemodialysis initiation (9.1% vs. 2.3%, p = 0.029) and inflammatory activity were higher in normouricemic patients than in hyperuricemic patients. The frequency of renal insufficiency was lower in normouricemic patients (25.0% vs. 53.4%, p < 0.001). However, the recurrence rate of gout attack was not different between the two groups (24.7% vs. 33.0%, p = 0.220). In multivariate analysis, female sex, history of urinary stone, presence of tophi, and use of thiazide were associated with increase of recurrent gout attack, but not with serum urate status during an acute attack (hazard ratio, 1.075; 95% confidence interval, 0.972 to 1.190; p = 0.159). CONCLUSIONS: Normouricemia during an acute gout attack was more frequently observed in postsurgical episodes, hemodialysis initiation and patients with preserved renal function. While higher inflammatory activity was observed in normouricemic patients, recurrent attack was not associated with serum urate levels during an acute attack. Thus, careful follow-up should be considered in gout patients regardless of serum urate levels during an acute attack.